Optimizing The Utilization of Information and Communication Technology as Learning Resources in The Digital Era at SMPN 4 Bataguh - Nor Azizah; Maya Madina; Widy Noviani; Ahmad Suriansyah; Aslamiah Aslamiah (FKIP - Universitas Riau, 2026)
This study aims to describe the optimization of Information and Communication Technology (ICT) utilization as a learning resource in the digital era at SMPN 4 Bataguh. The research focuses on teachers’ strategies in utilizing ICT to support the effectiveness and interactivity of the teaching and learning process. A descriptive qualitative approach was employed, with data collected through observations, interviews, and documentation. The findings indicate that ICT has been applied in various forms, including online learning applications, interactive learning media, and digital-based academic administration. Nevertheless, the utilization of ICT has not been optimally implemented. Several obstacles were identified, such as limited internet infrastructure, differences in teachers’ digital literacy levels, and the absence of continuous professional training related to ICT use in learning. These conditions affect the consistency and effectiveness of ICT integration in classroom practices. Therefore, strengthening teachers’ digital competencies and improving ICT facilities are essential to support effective and sustainable learning processes.